The economics of military spending : a Marxist perspective - Elveren, Adem Y. (Adem Yavuz) (Abingdon, Oxon ; New York, NY : Routledge, 2019)
The Economics of Military Spending offers a comprehensive analysis of the effect of military expenditures on the economy. It is the first book to provide both a theoretical and anempirical investigation of how military spending affects the profit rate, a key indicator of the health of a capitalist economy. The book presents a general discussion on the economic models of the nexus of military spending and economic growth, as well as military Keynesianism and the military-industrial complex. Including an account of the Marxist crisis theories, it focuses on military spending as a counteracting factor to the tendency of rate of profit to fall. Using a range of econometric methods and adopting a Marxist perspective, this book provides comprehensive evidence on the effects of military spending on the rate of profit for more than thirty countries. The findings of the book shed light on the complex linkages between military spending and the profit rate by considering the role of countries in the arms trade. Offering a Marxist perspective and an emphasis on quantitative analysis, The Economics of Military Spending will be of great interest to students and scholars of defence and peace economics, as well as Marxist economics.
OCLC-licensed vendor bibliographic record.
Keywords: War -- Economic aspects; National security -- Economic aspects; Marxian economics; BUSINESS & ECONOMICS / Economics / General; BUSINESS & ECONOMICS / Reference; BUSINESS & ECONOMICS / General; BUSINESS & ECONOMICS / Economic History